UPAYA MENINGKATKAN KOMPETENSI DIGITAL GURU MELALUI PELATIHAN PENGGUNAAN LEARNING MANAGEMENT SYSTEM BERBASIS EDUKATI - Dahiana, Wa Ode; Anastasyia, Neneng; Mataheru, Eunike Ester (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of digital technology has brought significant changes in education, including in the learning process. However, teachers in remote areas such as Leihitu Barat District, Central Maluku, still face limitations in digital competence and infrastructure, which hinder the optimal use of educational technology. Based on these conditions, this community service program was carried out with the aim of improving teachers’ digital competence through training on the use of the Edukati-based Learning Management System (LMS). The activities involved several stages, including preparation, face-to-face training, hands-on practice using the LMS, online mentoring after the training, and evaluation through pre-test and post-test. The results indicated a significant improvement in participants’ understanding and skills. Before the training, all teachers had no knowledge of LMS and no prior experience in using it. After the training, all participants understood the basic functions of LMS, and 75% were able to operate Edukati’s key features, such as creating digital classes, uploading materials, and designing learning assessments. Teachers’ readiness level increased from 4.2% (not ready) to 82.1% (ready). Nevertheless, limited devices, unstable internet access, and the absence of technical staff remain challenges in implementation. Teachers’ enthusiasm, the support of a WhatsApp community, and the openness of partner schools to digital innovation provide opportunities for program sustainability. Therefore, the Edukati LMS training proved effective in improving teachers’ digital literacy and is essential as a strategic step to strengthen digital culture in education, particularly in remote areas